2019
DOI: 10.1186/s13014-019-1378-x
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus hypofractionated postmastectomy radiotherapy: a report on long-term outcomes and late toxicity

Abstract: Objective We evaluated the long-term outcomes and late toxicity of conventional fractionated (CF) and hypofractionated (HF) postmastectomy radiotherapy (PMRT) in terms of locoregional recurrence-free survival (LRRFS), disease-free survival (DFS), overall survival (OS), and late toxicity. Methods A cohort of 1640 of breast cancer patients receiving PMRT between January 2004 and December 2014 were enrolled. Nine hundred eighty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…39,40 As a result, an increasing number of patients have become eligible to receive comprehensive regional nodal irradiation after breast conservation or PMRT. Unfortunately, hypofractionated nodal irradiation has yet to see widespread adoption in the United States, although a nascent literature does suggest it is safe to employ 40 Gy in 15 daily fractions targeting the breast/chest wall and regional nodes (presuming the supraclavicular hotspot is below 105%; otherwise, 39 Gy in 15 fractions is preferred), 33,[41][42][43] with ongoing studies using this regimen in a randomized fashion to suggest true clinical equipoise (RT-CHARM: NCT03414970; FABREC: NCT03422103). The UK FAST FORWARD trial includes a 5-fraction lymphatic RT cohort, but this is not yet considered safe outside of a trial or in the setting of palliation.…”
Section: Whole-breast Rt and Hypofractionated Regimensmentioning
confidence: 99%
“…39,40 As a result, an increasing number of patients have become eligible to receive comprehensive regional nodal irradiation after breast conservation or PMRT. Unfortunately, hypofractionated nodal irradiation has yet to see widespread adoption in the United States, although a nascent literature does suggest it is safe to employ 40 Gy in 15 daily fractions targeting the breast/chest wall and regional nodes (presuming the supraclavicular hotspot is below 105%; otherwise, 39 Gy in 15 fractions is preferred), 33,[41][42][43] with ongoing studies using this regimen in a randomized fashion to suggest true clinical equipoise (RT-CHARM: NCT03414970; FABREC: NCT03422103). The UK FAST FORWARD trial includes a 5-fraction lymphatic RT cohort, but this is not yet considered safe outside of a trial or in the setting of palliation.…”
Section: Whole-breast Rt and Hypofractionated Regimensmentioning
confidence: 99%
“…Multiple randomized trials compared normofractionated (25-28 Fractions in 1.8-2.0 Gy single doses) to hypofractionated RT schedules (single doses > 2.0 Gy in 15-16 fractions) [28,29]. Overall, fraction sizes greater than 2.0 Gy did not affect local recurrence, was associated with decreased acute toxicity and did not affect breast cosmesis, late toxicity or quality-of-life [30,31]. These shorter regimens have been adopted mainly for lower risk patients after breast conserving surgery (BCS) but not thoroughly in PMRT with treatment of the RNI due to concerns regarding risk of lymphedema and brachial plexopathy.…”
Section: Hypofractionated Post-mastectomy Radiotherapymentioning
confidence: 99%
“…There is growing interest in continuing study of hypofractionation after postmastectomy [10]. Emerging evidence has suggested that postmastectomy HFRT may be as effective as CFRT for patients at high risk of locoregional recurrence [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%